2017
DOI: 10.1097/spv.0000000000000337
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Regulation of Connective Tissue Metabolism Genes in Women With Pelvic Organ Prolapse

Abstract: Objective To compare differences in expressions and relationships between key genes involved in extracellular matrix metabolism and tissue cellularity in women with and without pelvic organ prolapse (POP) Methods A total of 80 biopsies (anterior cuff, posterior cuff, and/or leading edge) were obtained from 30 women: n=10 premenopausal without POP (controls), n=10 premenopausal with POP, and n=10 postmenopausal with POP. Quantitative reverse-transcriptase polymerase chain reaction was used to assess gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 58 publications
0
5
0
2
Order By: Relevance
“…Chtistian et al [6] compared the difference in collagen metabolism between control and POP patients in both USL and vaginal tissue and found a significant increase in pro-MMP-2 expression, but the differences were not statistically significant in USL. Another study [24] obtained a vaginal wall biopsy from three sites (leading edge, anterior and posterior cuffs) at the time of hysterectomy. Interestingly, it was found that COL1, TIMP2 and TIMP3 were all significantly downregulated in the leading edge compared to the posterior cuff in postmenopausal POP women, but no significant differences were found between the posterior cuff and anterior cuff biopsies in any group.…”
Section: Discussionmentioning
confidence: 99%
“…Chtistian et al [6] compared the difference in collagen metabolism between control and POP patients in both USL and vaginal tissue and found a significant increase in pro-MMP-2 expression, but the differences were not statistically significant in USL. Another study [24] obtained a vaginal wall biopsy from three sites (leading edge, anterior and posterior cuffs) at the time of hysterectomy. Interestingly, it was found that COL1, TIMP2 and TIMP3 were all significantly downregulated in the leading edge compared to the posterior cuff in postmenopausal POP women, but no significant differences were found between the posterior cuff and anterior cuff biopsies in any group.…”
Section: Discussionmentioning
confidence: 99%
“…In the molecular function category, the terms were ‘cytoskeletal protein binding’, ‘actin binding’, ‘calmodulin binding’, ‘GTPase regulator activity’, ‘calcium channel activity’, ‘calcium-release channel activity’ and ‘protein binding’. Similarly, previous evidence has demonstrated that several families, including collagen (2022), LOX (15,2325) and fibulin (25), have important roles in the synthetic metabolism and pathogenesis of POP; however, in the catabolism of the pathogenesis of POP, matrix metalloproteinase (2630) and tissue inhibitors of metalloproteinase serve vital roles (27,30). In the regulation of anabolic and catabolic processes, the homeobox gene family is key (31,32).…”
Section: Discussionmentioning
confidence: 78%
“…Perhaps the future of prolapse management should focus on disease prevention and advancing understanding of pathophysiology of POP, including role of collagen, connective tissue, nerve and muscle injury, and regeneration. Increasingly, investigators are looking for genetic variations that predispose women to early-onset prolapse with the hope that these genes can be selected out in future generations 85. Until these novel pathways of prevention and treatment reach patient application, it is important that a surgeon managing pelvic organ prolapse understands the array of options available for treating prolapse and is able to guide a patient’s decision-making with the available evidence on outcomes and risks.…”
Section: The Futurementioning
confidence: 99%